Strategi Pengembangan Ekonomi Masyarakat di Desa Sintuwulemba, Kecamatan Lage, Kabupaten Poso - Mouto, Patrik Rivaldo; Taaha, Yulian Rinawaty; Pasambaka, Yohanes (Fakultas Ekonomi Universitas KristenTentena, 2024)
This study examines the strategy for developing the community economy in Sintuwulemba Village, Lage District, Poso Regency. The research adopts a qualitative approach and was conducted from July to August 2024. Data were collected through interviews, observation, and document analysis, with informants including village officials and residents. Findings indicate that utilizing natural resources in agriculture and animal husbandry and enhancing human resources through training are effective strategies. The study highlights innovative programs, including agrotourism and sustainable agricultural practices, that have improved economic welfare. These initiatives are supported by village infrastructure and a participatory planning approach, enhancing self-sufficiency and economic resilience.